On the convergence of the Newton's method in the interval symmetric single step procedure - Mohammad Rusli, Syaida Fadhilah; Monsi, Mansor; Hassan, Nasruddin (Hikari, 2014)
The rate of convergence of the interval symmetric single-step procedure IMW is increased by introducing a Newton’s method (NM) at the beginning of the procedure. The numerical convergence of this new procedure called INSMW is shown. Based on the numerical results, this new procedure performed better than does IMW, verifying the rate of convergence to be at least four.